HPV Infection in a Cohort of HIV-Positive Men and Women: Prevalence of Oncogenic Genotypes and Predictors of Mucosal Damage at Genital and Oral Sites. (5th March 2013) - Marchetti, Giulia; Comi, Laura; Bini, Teresa; Rovati, Marco; Bai, Francesca; Cassani, Barbara; Ravizza, Marina; Tarozzi, Marco; Pandolfo, Alessandro; Dalzero, Serena; Opocher, Enrico; Romagnoli, Solange; et al.
Abstract : The aim of this study was to assess the prevalence of HPV infection and determinants of abnormal cytology in HIV-positive patients. In a cross-sectional study, patients of both sexes, asymptomatic for HPV, underwent anorectal (men)/cervical (women) and oral swabs. Cytology and HPV-PCR detection/genotyping (high- and low-risk genotypes, HR-LR/HPV) were performed. A total of 20% of the 277 enrolled patients showed oral HPV, with no atypical cytology; in men, anal HPV prevalence was 81% with 64% HR genotypes. In women, cervical HPV prevalence was 58% with 37% HR-HPV. The most frequent genotypes were HPV-16 and HPV-18; 37% of men and 20% of women harbored multiple genotypes. Also, 47% of men showed anal squamous intraepithelial lesions (SILs); 6% had high- and 35% low-grade SILs (HSILs/LSILs); 5% had atypical squamous cells of undetermined significance (ASC-US). HR-HPV was independently associated with anal-SIL in men (P = 0.039 ). Moreover, 37% of women showed cervical SIL: 14 ASC-US, 15 LSILs, 4 HSILs, and 1 in situ cancer. The presence of both LR and HR-HPV in women was independently associated with SIL (P = 0.003 andP = 0.0001 ). HR-HPV and atypical cytology were frequently identified in our cohort. HPV screening should be mandatory in HIV-infected subjects, and vaccine programs for HPV-negative patients should be implemented.